Representations and practices of patients with vasculogenic ulcers on quality of life - Nathália Nunes Gomes; Lara Mariana Monteiro de Santa Rosa; Márcia de Assunção Ferreira; Rafael Celestino da Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To identify the social representations and practices of patients with vasculogenic ulcer about their quality of life. Method: Qualitative research that applied the Social Representations theory. Participants were 30 patients with vasculogenic ulcers registered at a health unit in Rio de Janeiro. Data was collected through semi-structured interviews, and lexical analysis was applied. Results: The social representations about the quality of life of the patients were built from the affections arising from the changes in their lives. Thus, losses arising from the reconfiguration of daily life led to a negative symbolic construction about themselves and their lives, which resulted, on the one hand, in proactive self-care behaviors and, on the other, in less self-care. Conclusion: Care for health promotion and social support is required to re-signification of life with ulcer and the adoption of new coping practices.